Conversations with Shotetsu - Brower, Robert H. (Michigan Monograph Series in Japanese Studies, 2020)
Shotetsu monogatari was written by a disciple of Shotetsu (1381-1459), whom many scholars regard as the last great poet of the courtly tradition. The work provides information about the practice of poetry during the 14th and 15th centuries, including anecdotes about famous poets, advice on how to treat certain standard topics, and lessons in etiquette when attending or participating in poetry contests and gatherings. But unlike the many other works of that time that stop at that level, Shotetsu's contributions to medieval aesthetics gained prominence, showing him as a worthy heir-both as poet and thinker-to the legacy of the great poet-critic Fujiwara no Teika (1162-1241). The last project of the late Robert H. Brower, Conversations with Shôtetsu provides a translation of the complete Nihon koten bungaku taikei text, as edited by Hisamatsu Sen'ichi. Steven D. Carter has annotated the translation and provided an introduction that details Shôtetsu's life, his place in the poetic circles of his day, and the relationship of his work to the larger poetic tradition of medieval Japan. Conversations with Shotetsu is important reading for anyone interested in medieval Japanese literature and culture, in poetry, and in aesthetics. It provides a unique look at the literary world of late medieval Japan.